Attractiveness dan Buying Decision: Peran Moderasi Competitive Advantage dalam Perspektif Manajemen Bisnis Syariah - Ainurridho, Husni; Suhendar; Restie Utamie, Zathu (Kartika: Jurnal Studi Keislaman, 2025)
This study aims to examine the relationship between attractiveness and buying decision, with competitive advantage as a moderating variable within the perspective of Sharia business management. The research was conducted on consumers of “Sahabat” Beef and Meatball Milling Kiosk located in Pringsewu, Indonesia. Using a quantitative approach, data were collected through a structured questionnaire distributed to 100 respondents selected by purposive sampling. The data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4 to test validity, reliability, and the structural relationships among variables. The findings reveal that attractiveness has a positive and significant effect on buying decision. Furthermore, competitive advantage significantly moderates this relationship, indicating that a stronger competitive advantage enhances the influence of attractiveness on consumer purchasing decisions. These results highlight the importance of integrating Sharia-compliant values into marketing strategies, emphasizing ethical appeal, product integrity, and spiritual value as key factors that strengthen consumers’ decision-making processes in Islamic business contexts.